2018
DOI: 10.1007/s40801-018-0138-9
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Adverse Effects of Capecitabine Toxicity in an Elderly Population

Abstract: BackgroundFew studies have assessed the safety and effectiveness of the numerous available chemotherapeutic therapies for geriatric oncology patients. Most safety studies are conducted in large trials, and there is some uncertainty surrounding whether the results would be the same in typical daily use.ObjectiveThis retrospective study aims to assess the adverse effects of real-world capecitabine use in elderly patients.MethodsWe reviewed the records of patients treated with capecitabine in an oncology departme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 25 publications
0
2
2
1
Order By: Relevance
“…The percentage of older adults who reported moderate-severe fatigue in this study (about 40%) was higher than that reported in the literature (about 25%) [ 29 ]. However, the number of older adults who rated their HFS as severe or extremely severe in this study (7%) was lower than those reported in a previous randomized controlled trial or a chart review study (21%) [ 30 , 31 ]. Such differences may be because of proactive HFS monitoring and management strategies in clinical practice or the small sample of older adults (n = 43, 44%) with a limited representation.…”
Section: Discussioncontrasting
confidence: 82%
“…The percentage of older adults who reported moderate-severe fatigue in this study (about 40%) was higher than that reported in the literature (about 25%) [ 29 ]. However, the number of older adults who rated their HFS as severe or extremely severe in this study (7%) was lower than those reported in a previous randomized controlled trial or a chart review study (21%) [ 30 , 31 ]. Such differences may be because of proactive HFS monitoring and management strategies in clinical practice or the small sample of older adults (n = 43, 44%) with a limited representation.…”
Section: Discussioncontrasting
confidence: 82%
“…The number is higher than what a previous study has reported that 25% of patients rated their fatigue as moderate-severe when taking oral chemotherapy [27]. While 7% of older adults rated their HFS as severe or extremely severe in the current study, this was less than 21% older adults reported in a previous randomized controlled trial [28], and 11% of older adults aged older than 70 years reported in a chart review study [29]. Such differences may be because the sample size of the current study was small, and the sample of participants aged 65 years and above was limited.…”
Section: Discussioncontrasting
confidence: 84%
“…In addition, consistent with other studies [ 22 , 23 ], our study showed a significant association between HFS and increasing age. Older patients often present with pre-existing comorbidities and are prescribed with multiple concurrent medications [ 22 , 24 ]. Furthermore, a study showed that elderly patients may have reduced drug clearance, leading to higher capecitabine exposure compared to younger individuals [ 25 ].…”
Section: Discussionmentioning
confidence: 99%